FDI technology spillovers in the mining industry: Lessons from South Africa's mining sector. (August 2019) - Ghebrihiwet, Nahom
Abstract: Resource-rich countries are increasingly aiming to benefit from technology and knowledge spillovers in their extractive industries. In order to enhance knowledge spillovers, host country governments require natural resources companies to hire and train local workers, to engage in supplier development programs, and to be active in cooperative research agreements with local partners. Based on the South African innovation survey, this paper shows that companies active in the natural resources sector will more likely introduce product or process innovations if they engage in cooperative research agreements with foreign customers or suppliers. Furthermore, compared to mining companies and downstream firms, mining suppliers are more likely to introduce product innovations that are new to the market. Furthermore, the absorptive capacity of firms, proxied by a firm's own investment in R&D is an important determinant of both product and process innovations by firms in the mining sector. Finally, firms with more skilled workers will more likely introduce new or significantly improved services.